Scheduling Sustainable Homecare with Urban Transport and Different Skilled Nurses Using an Approximate Algorithm - Ros-McDonnell, Lorenzo; Szander, Norina; de-la-Fuente-Aragón, María Victoria; Vodopivec, Robert (Sustainability, 2019)
The essential characteristics that distinguish homecare services from other routing and scheduling problems are relatively few patients being spread out over a large urban area, long transport times and several different services being provided. The approach that the authors present herein was developed to solve planning homecare services according to the criterion of increasing social sustainability and incorporating environmentally sustainable transport systems. The objective of this paper is to present a tool to plan the daily work carried out by a homecare service with assigned patients with specific care requirements. It relies on the resources of nurses with different qualifications by assuming costs that depend on both offering the service and the different chosen transport modes. The algorithm manages several priority rules by ensuring that homecare provider goals and standards are met. The developed algorithm was tested according to the weekly homecare schedule of a group of nurses in a medium-sized European city and was successfully used during validation to improve homecare planning decisions. The results, therefore, are not generalisable but its modular structure ensures its applicability to different cases. The algorithm provides a patient-centred visiting plan and improves transport allocation by offering nurses a better route assignment by considering the required variables and each nurse’s daily workload.